Pengaruh Latihan Kesimbangan dan Ankle Strategy Exercise Terhadap Risiko Jatuh Pada Lansia - Riskah Nur’amalia; Meutiah Mutmainnah; Anggun Indah Lestari; Sulastri Sulastri (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction: Elderly people who have health problems are said to be more vulnerable (frailty). One aspect that causes the elderly to experience vulnerability is the high risk of falling. Aim: Determine the effect of balance training and Ankle Strategy Exercise on the risk of falls in the elderly. Methods: Using comparative analytic research one group pretest-posttest design Population pre-elderly 50-60 years and elderly >60 years, sampling with a purposive sampling technique that met the inclusion criteria. Data collection with the Timed Up and Go Test (TUG) instrument. Results: Showed that the value of p = 0.000 (p <0.05). Conclusion: There is an effect of giving balance exercises and ASE on the risk of falling in the elderly.